Enhancing Professional Competencies Through Soft Skills Development - Paneru, Narendra Raj (Educational Journal, 2026)
In today’s world, mere technical expertise is not sufficient for effective performance in educational and professional contexts. In this case, soft skills such as effective communication, collaboration, creativity, critical thinking, teamwork, leadership and problem-solving have emerged as crucial determinants of professional competencies and workplace performance. Within this understanding, this study explores the role of soft skills in enhancing professional competencies among English language teachers in Nepal. Adopting an interpretive qualitative research design, six secondary-level experienced teachers teaching English language in community schools were purposively selected for in-depth interviews. The gathered qualitative information was then thematically analyzed in five thematic headings. The findings of the study revealed that teachers intuitively practice soft skills as their professional practices, though their formal awareness is varied. Furthermore, the study identifies key competencies that teachers acquire through both formal training and self-directed learning, such as communication skills, interpersonal abilities, leadership quality, problem-solving capacity, critical thinking and rapport building. Finally, the findings of the study indicate reciprocal relationships between soft skills and professional development, which cultivates the personality of teachers and enhances classroom effectiveness, collaboration, and holistic professional growth.